Changes of natural killer cells’ phenotype in patients with chronic hepatitis B in intermittent interferon therapy - Bi, Xiaoyue; Xie, Si; Wu, Shuling; Cao, Weihua; Lin, Yanjie; Yang, Liu; Jiang, Tingting; Deng, Wen; Wang, Shiyu; Liu, Ruyu; Gao, Yuanjiao; Shen, Ge; et al. (Frontiers in Immunology, 2023)
Background To investigate the changes of natural killer (NK) cell phenotype in the interferon alpha (IFN-α) treatment of chronic hepatitis B (CHB) and its relationship with clinical indicators. Methods The CHB patients who did not receive any antiviral treatment were set as initial treatment group and used pegylated interferon alpha (PEG-IFN α). Peripheral blood samples were collected at baseline, 4 weeks, and 12-24 weeks. For IFN-treated patients who entered the plateau were set as plateau group, and PEG-IFN α was discontinued and resumed after an interval of 12-24 weeks. Besides, we also enrolled some patients who had received oral drug for more than 6 months as oral drug group without follow up. Peripheral blood was collected during the plateau period, which was set as baseline, and after 12-24 weeks of intermittent treatment, and after 12-24 weeks of additional treatment with PEG-IFN α. The aim of the collection was to detect hepatitis B virus (HBV) virology, serology and biochemical indicators, and the NK cell related phenotype was detected by flow cytometry. Results In the plateau group, subgroup of CD69+CD56dim was higher with statistical significance when comparing with the initial treatment group and oral drug group [10.49 (5.27, 19.07) vs 5.03 (3.67, 8.58), Z = -3.11, P = 0.002; 10.49 (5.27, 19.07) vs 4.04 (1.90, 7.26), Z = -5.30, P < 0.001)]. CD57+CD56dim was significantly lower than that in initial treatment group and oral drug group respectively [68.42±10.37 vs 55.85±12.87, t = 5.84, P < 0.001; 76.38±9.49 vs 55.85±12.87, t = -9.65, P < 0.001]. The CD56brightCD16- subgroup in the plateau group was higher with statistical significance compared with initial treatment group and oral drug group respectively [11.64 (6.05, 19.61) vs 3.58 (1.94, 5.60), Z = -6.35, P < 0.001; 11.64 (6.05, 19.61) vs 2.37 (1.70, 4.30), Z = -7.74, P < 0.001)]. CD57+CD56dim in the plateau group had a significant higher percentage than that at baseline after IFN discontinuation for 12-24 weeks (55.85±12.87 vs 65.95±12.94, t = -2.78, P = 0.011). Conclusion During the long-term treatment of IFN, the killer subgroup of NK cells is continuously depleted, leading to the differentiation of the regulatory subgroup into the killer subgroup. In the killing subgroup, although the number is continuously depleted, the activity of the subgroup is continuously increased. In the plateau phase, after stopping IFN for a period of time, the number of NK cell subsets would gradually recover, but was still lower than that in the initial treatment group.